Titanium dioxide and zinc oxide nanoparticles affect some bacterial diseases, and growth and physiological changes of beetroot. Issue 5 (3rd September 2019) - Siddiqui, Zaki A.; Khan, Manzoor R.; Abd_Allah, Elsayed F.; Parveen, Aiman
ABSTRACT: Nanoparticles (NPs) have been applied for management of pathogenic microbes affecting agricultural crops. Pectobacterium betavasculorum (Thomson et al., 1984) Gardan et al., 2003, Xanthomonas campestris pv. beticola (Pammel) Dowson, and Pseudomonas syringae pv. aptata (Brown and Jamieson) Young, Dye, and Wilkie are bacterial pathogens of beetroot ( Beta vulgaris L.) and a concern for its sustainable cultivation. Effects of titanium dioxide (TiO2 ) and zinc oxide (ZnO) NPs at 0.25 and 0.50 mL∙L −1 were determined on P. betavasculorum, X. campestris pv. beticola, and P. syringae pv. aptata, and on growth, chlorophyll and carotenoid contents, superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), phenylalanine ammonia-lyase (PAL), glutathione (GSH), proline, H2 O2, and malondialdehyde (MDA) contents of beetroot. Inoculation of beetroot with P. betavasculorum, X. campestris pv. beticola, and P. syringae pv. aptata reduced plant growth, and chlorophyll and carotenoid contents, but increased SOD, CAT, APX, PAL, GSH, proline, H2 O2, and MDA. Application of TiO2 or ZnO NPs to plants with, or without, bacteria increased plant growth, chlorophyll, carotenoid, SOD, CAT, APX, PAL, GSH, proline and H2 O2 contents, but decreased MDA content. Use of ZnO NPs was better than TiO2 NPs in increasing plant growth, chlorophyll and carotenoid, SOD, CAT, APX, PAL, GSH, proline and H2 O2 contents. The higher concentrations of both NPs were better in increasing plant growth, chlorophyll and carotenoid, SOD, CAT, APX, PAL, GSH, proline and H2 O2 contents, and decreased MDA than the lower NP concentration. Soft rot and bacterial pocket indices caused by P. betavasculorum and X. campestris pv. beticola were 4 of 5; leaf spot index caused by P. syringae pv. aptata was 3 of 5. Disease indices were reduced to 1 of 3/4 when 0.50 mL∙L −1 ZnO NPs was applied to plants challenged with bacterial pathogens. The ZnO NPs produced greater increase in plant growth and reduced disease indices than did TiO2 NP, and may be used for management of bacterial diseases of beetroot.